Appraisal of Bhatta Waste as an Admixture for the Stabilization of Fill Soil - Umar, Muhammad; Haider, Muhammad Arslan; Engr. Moin-ud-Din, (International Journal of Scientific Research and Management (IJSRM), 2024)
Testing of soil and knowing its strength parameter’s is one of the basic components in construction. Testing of soil is carried out to find whether the existing soil can endure the burden of structure withheld upon it or not. In case of a weak soil, one can find difficult to pursue construction or any development project. While talking of solutions, there are many methods to improve its strength and properties: one of them which we decided to work on is ‘Appraisal of Bhatta Waste as an Admixture for the Stabilization of Fill Soil’. It’s a kind of cost effective & economical means of improving soil, as the basic material required for stabilization is Bhatta waste, which is normally easily available material. The main objective of our test is to check the effectiveness of Bhatta waste on mechanical properties of filled material. The testing comprised of performing Atterberg limit, UCS, direct shear test, sieve analysis, Moisture dry density and Permeability test. The Bhatta waste passing no. 40 sieve is mixed with fill soil and testing on different proportions was carried out. Summary was prepared for explanation of engineering properties of different proportions, while further testing on higher proportions is recommended.